MAKNA TANDA KOMUNIKASI INTERPERSONAL AYAH DAN ANAK PADA FILM NANNY MCPHEE: SEMIOTIKA ROLAND BARTHES - Anggraini, Raissa Syifa; Kartikawangi, Dorien (Universitas Andalas, 2024)
Recognizing film as a potent medium of expression, the research underscores the profound impact of visual and auditory storytelling in conveying intricate messages through language used. Through the lens of Roland Barthes semiotic theory, this research endeavors to unravel the complexities embedded within familial communication, especially using informal language. Drawing upon theories of mass communication, media studies, and interpersonal dynamics, the qualitative methodology employed in this study entails a meticulous examination of 20 pivotal scenes encapsulating father-child interactions. Viewing Nanny McPhee through a semiotic lens unveils layers of meaning, encompassing denotation, connotation, and myth. Over a span from August 28, 2023, to November 10, 2023, the researcher meticulously observed and analyzed the nuances of familial communication depicted in the film. By capturing and dissecting scenes through Barthes theoretical framework, the study unveils prevalent themes such as misunderstandings, self-centeredness, and the repercussions of ineffective communication within family dynamics. Drawing from the research findings, it can be concluded that within the narrative of Nanny McPhee, a plethora of communication pitfalls emerge, including (1) instances of misunderstanding, (2) a pronounced focus on self-interest, (3) a reluctance to entertain external perspectives, (4) unilateral decision-making devoid of discourse, and (5) an overall deficiency in familial communication. Furthermore, the absence of paternal guidance and attention looms large, wielding considerable influence over the behavioral and developmental trajectories of the children depicted in the film.